EMERGING TRENDS IN API GATEWAYS FOR CLOUD MICROSERVICES: A TECHNICAL DEEP DIVE - VijayKumar Pasunoori (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive technical analysis examines the evolving landscape of API gateway technologies in cloud-native microservices architectures. The article presents quantitative evidence of significant market growth, with the global API management sector projected to reach USD 11.82 billion by 2028, representing a CAGR of 20.4%. Through detailed performance metrics and empirical analysis, article demonstrate how modern API gateways have transcended their traditional role as reverse proxies to become sophisticated infrastructure components managing complex orchestration, security, and optimization tasks. The article explores key technological advancements including service mesh integration, which shows 57% improvement in resource utilization, serverless capabilities achieving 99.95% scaling accuracy, and edge computing implementations reducing latency by 58%. Additionally, the article examines the integration of AI/ML capabilities, demonstrating 38% reduction in response times, and analyzes emerging trends in security and compliance, including zero-trust architectures processing 1.9 million authentication requests per minute. The article findings indicate that these developments collectively enable organizations to handle unprecedented scale while maintaining sub-100ms response times and 99.99% availability.